Implementasi Design Thinking Dalam Membangun Rancangan Ide Inovasi Model Bisnis Borneo Box: Aplikasi Distribusi Produk Pertanian Khusus Daerah Kalimantan Timur - Sherlinda Fadhillah Tanjung (Universitas 45 Surabaya, 2024)
Indonesia is one of the second largest agricultural countries after China, which is well known throughout the world. However, the facts that occur in the field are not like that, in fact Indonesia still depends on other countries to meet domestic food needs. So, to overcome this problem, a draft idea for an innovative business model for agricultural product distribution applications was created that focuses on the East Kalimantan region, namely Borneo Box. This research aims to realize and find solutions to problems that occur by applying the Design Thinking method as a tool to solve problems. The results of research involving 38 respondents show that the Borneo Box application is the right solution to solve the problem of the unavailability of agricultural product distribution applications specifically for the East Kalimantan region.